Imperative Order on The Micro Teaching Class - Rini Agustina; Fitri Wulansari (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This study aims to describe imperative speech in the micro teaching subject. The type of research used is descriptive with a qualitative research form. The study population was 8 semester students of the sixth semester. The data collection technique uses note taking and documentary techniques in the form of video recordings. The data collection tool is in the form of the researcher himself as a key instrument assisted by writing instruments. The data analysis technique used is the interactive analysis technique with the stages of collecting data, reducing data, presenting data, and making conclusions. The research result obtained is that the use of imperative speech in the micro teaching subject has sixteen imperative pragmatic forms.